Analogues - Phillips, Lindsey Elizabeth, author; Bates, Haley, advisor; Coronel, Patricia D., committee member; Tornatzky, Cyane R., committee member; Eckman, Molly Jean, committee member (Colorado State University. Libraries, 2011)
Block by block, pixel by pixel, my three dimensional work suggests the framework of the virtual and how it has become increasingly routine to cross its borders. Handheld devices are our tangible windows to the cloud, a reminder that we still reside in a physical world. The use of wood and enamel accentuate the materiality of my pieces but also suggest a link to historical mosaic and stained glass work. The exponential evolution of technology is contrasted by the excessive manual fabrication within one piece. The two dimensional drawings are the cloud itself. They express the invisible narrative within a single device as well as the dialogue it has between other connected technologies. Just as the sculptures have been stripped of function to highlight their physicality, the drawings broadcast a corporeal familiarity onto an incomprehensible dimension.
Keywords: craft; metalsmithing; enamel